2001
DOI: 10.1038/modpathol.3880350
|View full text |Cite
|
Sign up to set email alerts
|

Protein Overexpression and Gene Amplification of c-erbB-2 in Pulmonary Carcinomas: A Comparative Immunohistochemical and Fluorescence In Situ Hybridization Study

Abstract: Amplification of the c-er bB-2 gene (located on 17q11.2-12) is accompanied by overexpression of its cell surface receptor product, p185 ERBB2 . In pulmonary carcinomas, however, there has been disagreement between the reported frequencies of gene amplification and overexpression. To clarify their relationship, the correlation between the cellular expression of p185 ERBB2 and the level of c-erb B-2 gene amplification was studied. A total of 195 pulmonary carcinomas (182 primary and 13 metastatic) were examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0
3

Year Published

2002
2002
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 14 publications
1
41
0
3
Order By: Relevance
“…Other studies, such as Hirashima et al (2001) and Cox et al (2001) also detected clustered amplification only in rare cases of NSCLC. Disomic status for chromosome 17 was only found in 16% of the NSCLC tumours included in our study.…”
Section: Molecular and Cellular Pathologymentioning
confidence: 79%
See 1 more Smart Citation
“…Other studies, such as Hirashima et al (2001) and Cox et al (2001) also detected clustered amplification only in rare cases of NSCLC. Disomic status for chromosome 17 was only found in 16% of the NSCLC tumours included in our study.…”
Section: Molecular and Cellular Pathologymentioning
confidence: 79%
“…However, because of the strong intensity of the staining pattern, we classified these tumours as having 2+ results (Figure 1). This could give a slightly higher frequency of positive adenocarcinomas compared to other studies (Cox et al, 2001;Hirashima et al, 2001). However, the clinical significance of this scoring may not be relevant because 2+ tumours do not have a worse prognosis and may not have a significant benefit from HER-2/neu targeted therapy.…”
Section: Discussionmentioning
confidence: 92%
“…They further analyzed the 21 IHCpositive cases identified by FISH and reported that 3ϩ tumors possessed gene amplification but not 2ϩ or 1ϩ tumors, except 1 case of polyploidy. Hirashima et al 26 analyzed the copy number of the HER2 gene by FISH in 25 IHC-positive NSCLCs and found 2 tumors with high-level (about 9-fold) amplification and 3 tumors with low-level (Ͻ3-fold) amplification. In that study, high-level amplification was observed only in 2ϩ and 3ϩ tumors.…”
Section: Resultsmentioning
confidence: 99%
“…Besides being a poor prognosis marker (Dowsett et al, 2003), ERBB2 amplification is a predictive marker for targeted therapy with the monoclonal antibody trastuzumab in breast cancer patients with metastatic disease (Slamon et al, 2001). More recently, trastuzumab was shown to be effective as adjuvant treatment in breast-carcinoma patients with ERBB2 amplification/ overexpression (Piccart-Gebhart et al, 2005;Romond et al, 2005).Apart from breast cancer, ERBB2 amplification has been found in other malignant tumours, such as ovarian (McKenzie et al, 1993), lung (Hirashima et al, 2001), colon (Cohen et al, 1989), and gastric carcinomas (David et al, 1992). Earlier studies in gastric carcinomas reported ERBB2 overexpression using immunohistochemistry (IHC) in 5.2 -22.6% of the cases, whereas the proportion Translational Therapeutics with ERBB2 amplification evaluated using fluorescence in situ hybridisation (FISH) ranged from 3.8 to 12.2% (Takehana et al, 2002;Varis et al, 2004;Park et al, 2006;Kim et al, 2007).…”
mentioning
confidence: 99%
“…Apart from breast cancer, ERBB2 amplification has been found in other malignant tumours, such as ovarian (McKenzie et al, 1993), lung (Hirashima et al, 2001), colon (Cohen et al, 1989), and gastric carcinomas (David et al, 1992). Earlier studies in gastric carcinomas reported ERBB2 overexpression using immunohistochemistry (IHC) in 5.2 -22.6% of the cases, whereas the proportion Translational Therapeutics with ERBB2 amplification evaluated using fluorescence in situ hybridisation (FISH) ranged from 3.8 to 12.2% (Takehana et al, 2002;Varis et al, 2004;Park et al, 2006;Kim et al, 2007).…”
mentioning
confidence: 99%